Kepemimpinan Ideal dalam Islam: Perspektif Hadis Manajemen Pendidikan - Irfiaeh, Fauzia; Kasim, Amir A; Ramdhan, Dadan F (Melati Institute, 2024)
Leadership in Islam is a great responsibility that requires trustworthiness, accountability, and professionalism. This article discusses the concept of ideal leadership in Islam based on the perspective of educational management hadith. Through a qualitative approach and literature study, this research reveals that ideal leadership in Islam emphasizes strong moral and spiritual character. This article also discusses how these leadership principles can be applied in educational management to create an effective, fair, and spiritually-oriented system. The conclusion of this research is that ideal leadership has a significant influence on educational success, and therefore leaders in education must understand and implement Islamic leadership principles.